Reduction of ethanol emissions using manganese oxides supported metallic monoliths: a pilot-scale plant study - Peluso, Miguel Andrés (2013)
Metallic monoliths were prepared by anodized aluminum-scale pilot plant, using sulfuric acid as electrolyte. Anodisation tests were conducted at different times and different temperatures of the electrolytic bath. Aluminum monolith anodized at 40ºC for 30 min was selected for catalysts support. The monoliths were impregnated by two methods: i) impregnation in two stages using two Mn salts in an aqueous medium, and ii) impregnation using a KMnO4 solution in acetone. The last monolith presented a higher and a more homogeneous deposit of manganese oxide layer. The catalytic activity was tested in the total oxidation reaction of ethanol in a pilot-scale reactor at 50 L min-1, and ethanol concentrations of 900, 1800 and 3600 ppm. Monolith impregnated using acetone solution was more active that prepared in aqueous solution in all the experiments carried out.